2022
DOI: 10.1186/s13018-022-02946-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of motor imagery for improving functional performance after total knee arthroplasty: a systematic review with meta-analysis

Abstract: Background The aim of this study was to appraise the effects of motor imagery on the functional performance improvement among total knee arthroplasty patients systematically. We hypothesized a relatively greater recovery in the motor imagery group. Methods Medline (Ovid), Embase and Cochrane Controlled Register of Trials (CENTRAL) were searched from inception to October 1st, 2021. We included randomized controlled trials evaluating the effects of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Motor imagery refers to the mental representation of body movements without obvious body movements, which can effectively improve the performance of sports [ 34 ]. A systematic review shows that motion imagery is effective in the treatment of strength enhancement, pain reduction, and improved physical activity in patients undergoing TKA [ 35 ]. The intervention time of preoperative rehabilitation is generally 4–8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Motor imagery refers to the mental representation of body movements without obvious body movements, which can effectively improve the performance of sports [ 34 ]. A systematic review shows that motion imagery is effective in the treatment of strength enhancement, pain reduction, and improved physical activity in patients undergoing TKA [ 35 ]. The intervention time of preoperative rehabilitation is generally 4–8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al have conducted several clinical studies to evaluate the effect of neuromuscular exercise therapy on joint stability in patients with knee osteoarthritis [ 2 ]. Li et al, who aimed to systematically evaluate the effect of motor imagery on improvement in functional performance in patients with total knee arthroplasty, included randomized controlled trials evaluating the effect of motor imagery on motor imagery [ 3 ]. These articles have well explained the importance of protecting the knee, but they have not been studied on the basis of swimming movement under DM and have certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, all reviews assessed affected knee extension strength and timed up to go test. Two reviews assessed pain intensity assessed by Visual Analogue Scale (VAS) [10,11], while two studies assessed self-perceived knee function [9,10], and Paravlic et al [9] self-selected and brisk walking speed under dual and single tasks.…”
Section: Characteristics Of the Included Systematic Reviewsmentioning
confidence: 99%
“…The authors showed a promising result favoring cognitive interventions over routine physical therapy alone, taking into account overall physical function, maximal strength of the affected leg, fast walking speed, timed up-to-go test and active knee joint flexion. Two other reviews were published in last 2 years that examined a similar question [10,11]. These studies focused exclusively on MI practice only and included several different measures, such as range of motion of the affected knee joint and pain intensity.…”
Section: Introductionmentioning
confidence: 99%